Palestinians-Jews Conflict: Concern of the Voiceless - Merere, Ahmed (2004)
The conflict between Palestinians and Jews has remains one of the darkest spots of humanity for over 50 years now. On 11th September 2001, the World Trade Centre twin towers in New York, USA were blown off by two hijacked airliners in what the international community came to accept as a handiwork of terrorists. Immediately intelligence experts and anti-terrorists agencies worldwide came to think of only one group with such kind of ability, Osama bin Laden’s Al-Qaeda organization as the perpetrator. Bin Laden in turn sanctified the act as a method to fend the Palestinians in their war against Israel in so doing he is trying to justify his heinous and barbaric conduct through the suffering of other people, the Palestinians . His stands emanate from what he claims the US was bankrolling Israel's military campaign against the Palestinians in the West Bank and Gaza Strip. In other words Osama is trying to create more confusion in the already confusing quagmire. Basically this paper recapitulates the human tragedy and history of the Middle East not from scholarly point of view as the myth and reality, or as one-land two peoples but from a Common Man point of view from a far off countries, away from the point of conflagration. The segments of the paper include rationale as to why despite the evaporation of peace in the Middle East ordinary people who remains voiceless worldwide fathom solution is possible to the area. The presentation also give glimpse as to why change of fighting methods and the emergence of conspiracy of terrorists on Islamic clerical gowns are threatening the crumble of one of the biggest religion in the world, Islam. The paper also accounts for what may have been a vital threat facing Moslems worldwide today, ‘lack of laid down and internationally acceptable religious leadership’. The theory is Common Men and Women on the streets worldwide have some perception and opinion in relations to the Middle East Crisis and likewise they might provide the missing solution. The paper is of the opinion that besides experienced crises, the major challenges facing the world today is failure to learn how to listen and not heeding to the voiceless. The presenter looks on the common man perception as portrayed in the Tanzania media, Internet and other easily gauged international media. The Palestinians-Jews Conflict: Concern of the Voiceless is a media review that seeks out voice of the voiceless on a complex issue such as the Middle East crisis.